Integrating Green Ship Recycling into Indonesia’s Circular Economy Roadmap: A Geoda-Based Spatial Analysis - Shabrina, Nurul; Fitrinitia, Irene Sondang; Chotib, Chotib (Department of Urban and Regional Planning, Universitas Diponegoro, 2026)
Indonesia holds a strategic opportunity to develop Green Ship Recycling (GSR) as part of its transition toward a circular economy, particularly with the obligation to ratify the Hong Kong International Convention (HKC) 2009 by June 2025. However, GSR has not been fully integrated into the Circular Economy Roadmap 2025–2045, despite pressing issues of hazardous waste, material efficiency, and sustainable resource management. This study aims to demonstrate the crucial role of GSR in Indonesia’s circular economy and provide evidence-based policy recommendations for building a national GSR ecosystem. Data from 38 provinces were analyzed using GeoDa through multiple regression and spatial autocorrelation. The regression model shows a strong fit (R² = 0.829; Adjusted R² = 0.803; p < 0.001), with metal recyclers (β = 1.166), non-metal recyclers (β = 0.564), and hazardous waste facilities (β = 0.141) significantly supporting shipyard growth, while steel plants negatively affect development (β = –0.309). Spatial autocorrelation and LISA cluster analysis identified Riau Islands, East Java, Jakarta, and West Java as strategic hubs for GSR cluster development. The findings highlight those shipyards, recyclers, waste handlers, and steel manufacturers tend to cluster spatially, reinforcing the feasibility of establishing integrated GSR ecosystems in Indonesia. Such clustering could reduce dependence on volatile raw material imports by strengthening domestic recycled steel supply chains. Overall, this study provides empirical support for integrating GSR into Indonesia’s circular economy roadmap by enhancing cross-ministerial coordination, prioritizing cluster-based development, and ensuring alignment with HKC to promote sustainable and green ship recycling.